Participatory Governance in Agrotourism in Rumbia District Jeneponto Regency - Hamdan, Putri Ayu; Muh. Nur Yamin; Novayanti Sopia Rukmana; Andi Anugrah Mahyuddin (International Journal Of Public Policy and Bureaucracy, 2025)
This study aims to identify participatory governance in agritourism and its determinants in Rumbia District, Jeneponto Regency. It is a qualitative research type with a case study approach. Data collection techniques are done through observation, interviews, and documentation. The data analysis technique includes condensation, presentation, and conclusion drawing. The results showed that in the deliberation aspect, the implementation was exemplary. This can be seen from the active involvement of stakeholders and regular deliberations in both villages. In the action aspect, implementing the deliberation results has also been good, as evidenced by the community's involvement in developing agro-tourism and village cleanliness. However, there are infrastructure constraints in Kassi Village and land issues in Rumbia Village. The implementation has been exemplary in the monitoring aspect, as seen from the active role of the village head, Karang Taruna, and Pokdarwis in monitoring agritourism development. The implementation has also been exemplary in terms of coordination, with smooth coordination between village officials, the community, and external parties. In the aspect of democracy school, training and socialization have been good, conducted by the Youth and Sports Office and UNM Polytechnic. This can be seen from the community's enthusiasm for participating in the training. In terms of results, the impact of agritourism development has been good, as evidenced by the increase in MSMEs in Kassi Village and employment opportunities in Rumbia Village. Supporting determinant factors include good access to information through WhatsApp groups and training from village governments to improve community skills. Recommendations from this study are as follows: First, infrastructure improvements in Kassi Village, especially the road to the agritourism site, and the preparation of a more apparent master plan for broader agritourism development. Second, in Rumbia Village, agritourism management needs to be more professional and have more structured land management to support further development.